Reproductive agency and projects: Germans searching for egg donation in Spain and the Czech Republic - Bergmann, Sven (Reproductive biomedicine online, 2011)
German patients in search of IVF with egg donation (which is prohibited by German law) are increasingly deciding to travel to clinics in other countries (mostly to the Czech Republic and Spain) that are able to provide them with the eggs of other women. Through three case studies of German couples who crossed international borders for IVF with egg donation, this article provides insight into these transnational practices aiming to circumvent restrictions in reproduction, whatever they may be. The material for this article is based on ethnographic fieldwork and interviews conducted in Germany, Spain and the Czech Republic, as well as research undertaken on IVF internet bulletin boards. The concepts of 'reproductive agency' and 'reproductive projects' are used to analyse the ways in which people search for information about treatments and clinics in other countries, how they embed the practice into their daily lives and how they deal with and position themselves regarding the need for reproductive travel.
Keywords: rozhovory jako téma; Španělsko; dárci tkání; Germany; Female; Interviews as Topic; zdravotní turistika; Spain; vládní regulace; fertilizace in vitro; Government Regulation; ženské pohlaví; Tissue Donors; lidé; Německo; sběr dat; etnologie; Czech Republic; Data Collection; Internet; Česká republika; Ethnology; internet; Medical Tourism; Fertilization in Vitro; Humans